Reduction of the cardiac pulsation artifact and improvement of lesion conspicuity in flow‐compensated diffusion images in the liver—A quantitative evaluation of postprocessing algorithms. Issue 1 (11th September 2022) - Führes, Tobit; Saake, Marc; Lorenz, Jennifer; Seuss, Hannes; Stemmer, Alto; Benkert, Thomas; Uder, Michael; Laun, Frederik Bernd
Abstract : Purpose: To enhance image quality of flow‐compensated diffusion‐weighted liver MRI data by increasing the lesion conspicuity and reducing the cardiac pulsation artifact using postprocessing algorithms. Methods: Diffusion‐weighted image data of 40 patients with liver lesions had been acquired at 1.5 T. These data were postprocessed with 5 different algorithms (weighted averaging, p ‐mean, percentile, outlier exclusion, and exception set). Four image properties of the postprocessed data were evaluated for optimizing the algorithm parameters. These properties were the lesion to tissue contrast‐to‐noise ratio (CNR), the reduction of the cardiac pulsation artifact, the data consistency, and the vessel darkness. They were combined into a total quality score ( Q total, Q_total, set to 1 for the trace‐weighted reference image), which was used to rate the image quality objectively. Results: The weighted averaging algorithm performed best according to the total quality score ( Q total = 1.111 ± 0.067 Q_total=1.111± 0.067 ). The further ranking was outlier exclusion algorithm ( Q total = 1.086 ± 0.061 Q_total=1.086± 0.061 ), p ‐mean algorithm ( Q total = 1.045 ± 0.049 Q_total=1.045± 0.049 ), percentile algorithm ( Q total = 1.012 ± 0.049 Q_total=1.012± 0.049 ), and exception set algorithm ( Q total = 0.957 ± 0.027 Q_total=0.957± 0.027 ). All optimized algorithms except for the exception set algorithm corrected the pulsation artifact and increased the lesion CNR. Changes in Q total Q_total were significant for all optimized algorithms except for the percentile algorithm. Liver ADC was significantly reduced (except for the exception set algorithm), particularly in the left lobe. Conclusion: Postprocessing algorithms should be used for flow‐compensated liver DWI. The proposed weighted averaging algorithm seems to be suited best to increase the image quality of artifact‐corrupted flow‐compensated diffusion‐weighted liver data.